2018
DOI: 10.1177/1947603518756464
|View full text |Cite
|
Sign up to set email alerts
|

Articular Cartilage Lesion Characteristic Reporting Is Highly Variable in Clinical Outcomes Studies of the Knee

Abstract: Objective The purpose of this study was to investigate the degree of standardized evaluation and reporting of cartilage lesion characteristics in high-impact clinical studies for symptomatic lesions of the knee. We hypothesized that there are significant inconsistencies in reporting these metrics across orthopedic literature. Design A total of 113 clinical studies on articular cartilage restoration of the knee were identified from 6 high-impact orthopedic journals between 2011 and 2016. Full-text review was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…Thus, for example, age may not have been recognized to influence outcomes within the range of the population most commonly treated (patients <45 years old), but we cannot generalize the information to an older population that has not been studied. In addition, reporting of cartilage lesion characteristics and associated procedures is not ideal in the literature 48 and results in lower-quality studies, and we found that studies were inherently heterogeneous from different operative techniques performed for similar pathology. However, we still have, on average, studies with moderate quality (mean CMS, 71.76) included in this review, and there was no statistical difference among groups to bias our results.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, for example, age may not have been recognized to influence outcomes within the range of the population most commonly treated (patients <45 years old), but we cannot generalize the information to an older population that has not been studied. In addition, reporting of cartilage lesion characteristics and associated procedures is not ideal in the literature 48 and results in lower-quality studies, and we found that studies were inherently heterogeneous from different operative techniques performed for similar pathology. However, we still have, on average, studies with moderate quality (mean CMS, 71.76) included in this review, and there was no statistical difference among groups to bias our results.…”
Section: Discussionmentioning
confidence: 95%
“…While this review identifies a series of 12 studies that have documented clinical outcomes of pediatric and adolescent patients that underwent MFX, ACI, OCA, and OATS procedures, the literature remains nonstandardized in its reporting of specific clinical outcome scores. 31 This makes the objective comparison of results from different studies near impossible, thereby complicating clinical decision making. Small sample sizes in the remaining studies further complicate analysis by limiting the power of statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…The elementary functional unit of a tissue is the genetically and epigenetically variable cell, which manages the network that regulates all events in the biology or pathology of any particular organ tissue [ 13 ]. OA comprises a range of mild to advanced cartilage lesions and morphologic changes, combined with a long-lasting inflammatory microenvironment that contributes to cartilage degeneration, especially chondrocyte dysfunction, in the diseased joint [ 22 , 23 ]. Consequently, we attempted to identify onset cells that are highly sensitive to pathogenic factors during the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%